Social zooarchaeology : humans and animals in prehistory - Russell, Nerissa (Cambridge University Press, 2012)
"This is the first book to provide an overview and systematic examination of social zooarchaeology, a new approach that takes a holistic veiw of human-animal relations in the past. Until very recently, zooarchaeology was heavily focused on diet and subsistence economy, especially for prehistoric periods. This book argues that animals have always played much broader roles in human societies: as wealth, companions, spirit helpers, socrificial victims, totems, centerpieces of feasts, and objects of taboos, and so on. Exploring the briader significance of ancient animals provides a richer ppicture of past societies, Even those primarily interested in utuilitarian aspects of animal use need to account for that social factors that shaped zooarchaeological assemblages as much as taphonomic processes"--